2021
DOI: 10.3390/cells10113107
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Yield Stress of Sputum as a Relevant Biomarker in Cystic Fibrosis

Abstract: The mucus obstructing the airways of Cystic Fibrosis (CF) patients is a yield stress fluid. Linear and non-linear rheological analyses of CF sputa can provide relevant biophysical markers, which could be used for the management of this disease. Sputa were collected from CF patients either without any induction or following an aerosol treatment with the recombinant human DNAse (rhDNAse, Pulmozyme®). Several sample preparations were considered and multiple measurements were performed in order to assess both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…These results are in agreement with previous literature, where the viscosity of CF sputum was shown to be higher than healthy controls. 44 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with previous literature, where the viscosity of CF sputum was shown to be higher than healthy controls. 44 …”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with previous literature, where the viscosity of CF sputum was shown to be higher than healthy controls. 44 Biofilm formation in airway mimicking media is stable for at least 30 days of media storage at 4°C. Biofilm formation of PAO1 was measured over a month in the developed media stored at 4°C to test the stability of the airway mimicking media.…”
Section: Cf Media Becomes Viscous During Infection Reflecting Propert...mentioning
confidence: 99%
“…Additionally, the viscoelastic properties of the CF and healthy mucus-like hydrogels developed herein were within the same order of magnitude as the viscoelastic properties of CF and healthy airway mucus that have been analyzed and reported in literature. Recent sources have found that healthy and CF airway mucus have storage moduli within the range of 0.2 Pa to 93 Pa and loss moduli within the range of 0.1 Pa to 19 Pa 6,7 . The hydrogels developed here recapitulate the key differences in viscoelastic properties, mucin concentration, and solids concentration in physiological CF and healthy airway mucus.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, the results obtained from a dose escalation study (Figure S7) suggest that, although they are more sensitive than GL67A, CholP-based lipoplexes may retain some transfection efficiency under CF relevant conditions. This also suggests the requirement to further optimize CholP formulation, especially as regards its content in DP5K, and to investigate more complex cell culture models [70,71]. (ii) Considering bacterial infections that occur in the airways of CF patients, additional antibacterial properties of cationic lipids [18] or polymers [72] might be useful for CF lung gene therapy applications.…”
Section: Discussionmentioning
confidence: 99%